2001
DOI: 10.1359/jbmr.2001.16.10.1863
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Causes of Low Bone Density and Fractures in Kidney Transplant Patients

Abstract: Osteoporosis is known to occur in patients with kidney transplants, but limited information is available about the prevalence and causes of this complication. We asked all 330 patients with kidney transplants in our unit to participate in this study of whom 165 (50%) agreed to do so. The characteristics of the participating patients were similar to the remaining 165 nonparticipants. Seventy of 165 (42%) of the participants were women of whom 40 were postmenopausal in contrast to the men of whom only one was hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
73
1
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 17 publications
(20 reference statements)
6
73
1
10
Order By: Relevance
“…Ball et al (8) found that after 3 yr after kidney transplantation, the risk for hip fracture increased by 34% when compared with dialysis patients. Patel et al (9) evaluated 165 transplant patients and found evidence of osteoporosis, depending on gender or measured site, in 10 to 44% of the patients. Similarly, 27 (16%) patients had either vertebral deformities or a history of a low trauma fracture after transplantation.…”
Section: Is There An Increased Fracture Risk After a Kidney Transplant?mentioning
confidence: 99%
“…Ball et al (8) found that after 3 yr after kidney transplantation, the risk for hip fracture increased by 34% when compared with dialysis patients. Patel et al (9) evaluated 165 transplant patients and found evidence of osteoporosis, depending on gender or measured site, in 10 to 44% of the patients. Similarly, 27 (16%) patients had either vertebral deformities or a history of a low trauma fracture after transplantation.…”
Section: Is There An Increased Fracture Risk After a Kidney Transplant?mentioning
confidence: 99%
“…que os mais idosos, os pacientes com maior tempo de evolução da doença renal, aqueles submetidos a maior tempo de diálise, os transplantados há mais tempo, os pacientes que utilizaram a maior dose cumulativa de glicocorticóide e aqueles com elevados níveis séricos de marcadores de reabsorção óssea sofrem mais fraturas após o transplante renal. Nenhuma diferença foi encontrada a respeito da dose cumulativa de tacrolimus e ciclosporina (31). Em um estudo de coorte retrospectivo, Vantour e cols.…”
Section: Características Da Osteoporose Pós-transplante Transplante Runclassified
“…Остеопения, остеопоpоз и пеpеломы pазличной ло-кализации -частое осложнение после пересадки почки [9,16,17,18,21]. По данным одномомент-ных исследований, до 40-45% реципиентов как в ранние, так и отдаленные сроки после аллотpанс-плантации тpупной почки (АТП) имеют остеопе-нию, а от 10% до 50% пациентов -остеопороз [7,10,13,14].…”
unclassified
“…Снижение же МПК в области бедра может прогрессировать [12,19]. Потери костной ткани после АТП являются результатом нарушений процессов костного ремоделирования, большую роль в возникновении которых играют предшествующие пересадке почки почечная недостаточность и лечение ге-модиализом [14,17], иммуносупрессивная терапия (глюко-кортикоиды и циклоспорин) и вторичный гиперпаратиреоз [5,12,21]. Действительно, костная резорбция, по данным исследований биохимических маркеров костного обмена, усилена у большинства реципиентов АТП, в то время как костное формирование может быть повышенным, не нару-шенным либо сниженным [1,2,5,7,8,10,15].…”
unclassified
See 1 more Smart Citation